Digital Measurement of the Diameter of the Collagen Fibers by Transmission Electron Microscopy for Diagnosis of Ehlers-Danlos Syndrome-Like in Small Animals - Rossetto, Victor José Vieira; Ferranti, Camila Crepaldi; Firmo, Bruna Fernanda; Miazaki, Daniela Adachi; dos Santos, Daniela Carvalho; Sequeira, Júlio Lopes; Brandão, Cláudia Valéria Seullner (Acta Scientiae Veterinariae, 2021)
Background: Ehlers-Danlos-Like Syndrome (EDS) is a rare disease in small animals, whose diagnosis is based on the clinical findings and histopathological examination. The definitive diagnosis may require transmission electron microscopy. Despite this, the ultrastructural changes are poorly described in the literature. The aim of the present study is to describe the ultrastructural findings of collagen fibers and fibroblasts present in the dermis of two animals with EDS, and to evaluate the digital measurement of the diameter of the collagen fibers by transmission electron microscopic images. Cases: Two animals were evaluated with EDS by transmission electron microscopy. The first animal was an 1-year-old mixed breed female cat, due to spontaneous skin laceration, increased skin elasticity and an extensibility index corresponding to 25%. The second animal evaluated was a 5-month-old Golden Retriever female dog due to articular hypermobility, increased skin elasticity and an extensibility index corresponding to 16.6%. After a skin biopsy of the interscapular and lumbar regions, the samples were fixed in formalin 10% and glutaraldehyde for, respectively, histopathological examination by HE staining, and transmission electron microscopy. The histopathology of the affected cat revealed collagen fibers shortened and sometimes fragmented. The histopathology of the affected dog revealed disarranged and more eosinophilic staining collagen fibers. The collagen fibers were also of unequal sizes, shortened and slightly undulate. At the transmission electron microscopy of the affected cat was evidenced a greater spacing of the collagen fibers of variable diameters. Further this, the fibroblasts showed elongated nuclei with heterochromatic regions, which was surrounded externally by scant cytoplasm. The cytoplasm showed elongated and discrete organelles. At the transmission electron microscopy of the affected dog was evidenced a greater spacing of the collagen fibers of variable diameters. Further this, fibroblasts exhibited intense cytoplasmic vacuolization with similar appearance to that found in the dying process by autophagy. In addition, the images obtained by transmission electron microscopy were submitted to digital analysis to measure the diameter of the collagen fibers using the software Image J. For this purpose, it was obtained the average of the diameter of 10 collagen fibers in cross-section into four quadrants of 1μm each. The digital analysis of collagen fibers revealed significant alterations in the ultrastructure of collagen. In addition, it was verified cellular changes, such as the large amount of intracytoplasmic vesicles and the small amount of collagen fibers dispersed around the cells. Discussion: Microscopic abnormalities visualized by HE staining in this present study were compatible with the literature Transmission electron microscopy is fundamental to confirm the suspicion, since it revealed dermal alterations in the ultrastructure of collagen and fibroblasts. These findings indicate possible failure mechanisms of secretion and release of cellular products, as well as collagen. The digital measurement of the diameter of the collagen fibers contributed to the confirmation of the disease, since it was made randomly and reduced the subjectivity inherent of the evaluator. However, there are no studies using this method to allocate a range of significance for the diameter of collagen fibers that may be considered suggestive for the syndrome in small animals.